Kritisch én trouw - Hessel J. Zondag; Marinus H.F. van Uden (Religie & Samenleving)
This contribution deals with the question of commitment to the Roman Catholic Church after the crisis on sexual abuse. This question is answered through a survey among 131 Roman Catholics. Several aspects of commitment can be distinguished: being shocked by the abuse, accusations of laxness and carelessness of the Church, trust in the media, losing faith in the Catholic Church, doubting faith, and distancing from the Church. Our results prove that the respondents are critical on the one side and loyal on the other. A model in four stages for the loss of commitment is described: 1. finding out about the abuse; 2. criticism of the church; 3. losing faith, and 4. erosion of commitment. For women and those who know of victims of abuse this erosion of commitment occurs more frequently. For respondents with a theological background there is relatively less loss of commitment.